Grandmothering in Remission - Miller, Michelle Hughes (Journal of the Motherhood Initiative for Research and Community Involvement, 2018)
Xander, your Grandma is really sorry, but right now I can’t concentrate on this upcoming milestone in your life, your first birthday, because today I’m having my two year scans. In this personal narrative I explore grandmothering from a position of uncertainty— in this case cancer in remission. Using the framework of letters to my young grandson, I unpack my expectations for and experiences of the role of grandmothering, contextualized by my simultaneous effort to understand myself as a cancer survivor and the liminality of that particular status. How do I develop a relationship with my grandchild when he may not even have the memories of our interactions? How do I grandmother authentically while masking the health worries that sometimes threaten to consume me? How do I care for my daughter who has become a mother from a position of strength and confidence when the very ground I walk on feels unsettled and the future unclear? Considering issues of temporality, relationship directionality, caregiving, and authenticity, I place my musings as a grandmother and cancer survivor from my cancer journal, half-written letters, poetry, and reflective narrative into interaction.